The Heroic Client : a revolutionary way to improve effectiveness through client-directed, outcome-informed therapy - Duncan, Barry L., ....-; Miller, Scott D., 1949-; Sparks, Jacqueline A., ....- (San Francisco : Jossy-Bass, 2004)
The thoroughly revised edition of the book that will lead psychotherapy out of the stone age and into the age of the heroic client. This revised edition of The Heroic Client presents the latest empirical findings about what works in therapy-featuring the revolutionary increase in effectiveness achieved via client-based outcome feedback. Translating this research into pragmatic steps to enhance the benefit of any model of therapy, The Heroic Client calls for nothing less than a paradigm shift - a shift that not only improves outcome one client at a time but also assigns those we serve key roles in determining the way therapy is both delivered and funded.
Keywords: Psychotherapie -- algemeen